1997
DOI: 10.1038/bjc.1997.148
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial fluid pressure in intracranial tumours in patients and in rodents

Abstract: Summary Fluid transport parameters in intracranial tumours influence the delivery of therapeutic agents and the resolution of peritumoral oedema. The tumour and cortex interstitial fluid pressure (IFP) and the cerebrospinal fluid pressure (CSFP) were measured during the growth of brain and pial surface tumours [R3230AC mammary adenocarcinoma (R3230AC) and F98 glioma (F98)] in rats. Intratumoral and intracranial pressures were also measured in rodents and patients treated with dexamethasone, mannitol and furose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(106 citation statements)
references
References 36 publications
7
98
1
Order By: Relevance
“…The precise mechanism of this enlarged distribution after steroid use is not clear, however, dexamethasone may decrease the interstitial pressure and may provide better conditions for CED. Boucher et al (1997) demonstrated that the treatment with dexamethasone, mannitol, and fluosemide decreased the interstitial pressure in rodent intracranial tumor model. In this context, Yang et al (2014) demonstrated that pre-treatment with dexamethasone alone or in combination with mannitol and fluosemide increased the tumor carboplatin concentrations after intra-tumoral CED of carboplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism of this enlarged distribution after steroid use is not clear, however, dexamethasone may decrease the interstitial pressure and may provide better conditions for CED. Boucher et al (1997) demonstrated that the treatment with dexamethasone, mannitol, and fluosemide decreased the interstitial pressure in rodent intracranial tumor model. In this context, Yang et al (2014) demonstrated that pre-treatment with dexamethasone alone or in combination with mannitol and fluosemide increased the tumor carboplatin concentrations after intra-tumoral CED of carboplatin.…”
Section: Discussionmentioning
confidence: 99%
“…20 The chaotic structure of the vasculature, poor smooth muscle cell/pericyte coverage, and the dysfunctional ability of the endothelium to transport fluid create a high intratumoral pressure that perpetuates difficulties in perfusion of the growing tumor. [23][24][25] Due to the hyperpermeability of tumor vessels and the focal leaks often seen in tumor vessels, blood flow rates are reduced as measured by red blood cell velocity. 20,26 Studies have shown that tumors often have increased interstitial pressure 23 and that they can affect the interstitial pressure of surrounding normal tissue.…”
Section: The Tumor Vasculaturementioning
confidence: 99%
“…20,26 Studies have shown that tumors often have increased interstitial pressure 23 and that they can affect the interstitial pressure of surrounding normal tissue. 25 Hydraulic conductivity studies using intratumoral injection of Evans blue dye into tumor centers have shown that tumors vary in their resistance to fluid flow. 24 This resistance could be relieved using hyaluronase to hydrolyze the ECM, demonstrating that tumoral ECM composition and density influence interstitial pressure.…”
Section: The Tumor Vasculaturementioning
confidence: 99%
“…Recently, Iliff and colleagues delineated mechanisms of fluid drainage from the brain indicating that fluid flow pathways in perivascular spaces act like a brain lymphatic system clearing the brain interstitium (14). When a brain tumor develops, the flow patterns are disrupted because of tumor fluid drainage, cyst development, and edema-associated heightened interstitial pressures in the tumor as compared with the surrounding brain leading to flow from the tumor bulk (15,16). Tumors originating further from white matter tracts (conduits for fluid flow) have a better prognosis (17).…”
Section: Introductionmentioning
confidence: 99%